2014
DOI: 10.1007/s10973-014-4037-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical analysis of injection moulded poly(lactic acid) filled with poly(ethylene glycol) and talc

Abstract: In our research, the effect of talc particle size was analysed on the thermal and mechanical properties of renewable resource based, biodegradable polymer Poly(Lactic Acid) (PLA). Various talc particles with an average particle size of 24 μm, 1.9 μm, and 0.7 μm were blend mixed with PLA in 10 and 20 mass% containing no or an additional 10 mass% of Poly(Ethylene Glycol) (PEG) to increase molecular chain mobility. It was demonstrated that with decreasing talc particle size, its nucleation ability increased as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…Small quantities of talc added to the PLA matrix generally reduce the crystallization half times and decrease processing times [16]. A similar effect of talc on the crystallinity and mechanical properties of PLA/talc composites has been reported by several authors [17][18][19]. For example, Shakoor and Thomas [17] improved the Young's modulus from a value of 4.1 GPa for pure PLA, up to 9.8 GPa by addition of various contents of talc.…”
Section: Introductionsupporting
confidence: 68%
“…Small quantities of talc added to the PLA matrix generally reduce the crystallization half times and decrease processing times [16]. A similar effect of talc on the crystallinity and mechanical properties of PLA/talc composites has been reported by several authors [17][18][19]. For example, Shakoor and Thomas [17] improved the Young's modulus from a value of 4.1 GPa for pure PLA, up to 9.8 GPa by addition of various contents of talc.…”
Section: Introductionsupporting
confidence: 68%
“…A research on PLA doped with talc and poly ethylene glycol revealed that the crystallinity of the composite significantly increases up to 43.3% due to the nucleating effect induced by 0.7 lm talc particles in the presence of PEG (Tábi et al 2014). The addition of multiamide nucleating agent has also found to favour PLA crystallization by increasing the overall crystallization rate and hence transforming PLA into a promising engineering material (Wei et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true to those slowly crystallizing polymers such as polylactic acid [1][2][3][4][5][6][7][8][9][10], which can crystallize not only from the melt state but also from the glassy state, so-called melt and cold crystallization. In addition to its importance in the fundamental aspects, understanding the crystallization process and the phase structure is also critical in designing and optimizing polymer processing.…”
Section: Introductionmentioning
confidence: 99%